2015
DOI: 10.1371/journal.pone.0144934
|View full text |Cite
|
Sign up to set email alerts
|

Serum LncRNAs Profiles Serve as Novel Potential Biomarkers for the Diagnosis of HBV-Positive Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common malignancy that has a poor prognosis because there is lack of methods for early diagnosis. We aimed to utilize two serum long non-coding RNAs (lncRNAs), uc001ncr and AX800134, to diagnose hepatitis B virus (HBV)–positive HCC.MethodslncRNA microarrays were utilized to measure the differential expression of lncRNAs between tumor tissues and corresponding non-tumor tissues in HBV-positive hapatocellular carcinoma. uc001ncr and AX800134 were selected as candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 44 publications
0
40
0
1
Order By: Relevance
“…Since most protein-based assays lack the desired accuracy, ncRNA-based assays could be considered as an alternative diagnostic tool for HCC. Several studies suggested circulating ncRNAs [142][143][144][145][146][147][148][149][150][151][152][153][154][155] and tumor tissue derived ncRNAs [14][15][16][17]24,156 for HCC diagnosis or survival prediction. While tissue derived ncRNAs might be functionally relevant in the tumor, they are not necessarily good biomarkers for diagnosis.…”
Section: Ncrna Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most protein-based assays lack the desired accuracy, ncRNA-based assays could be considered as an alternative diagnostic tool for HCC. Several studies suggested circulating ncRNAs [142][143][144][145][146][147][148][149][150][151][152][153][154][155] and tumor tissue derived ncRNAs [14][15][16][17]24,156 for HCC diagnosis or survival prediction. While tissue derived ncRNAs might be functionally relevant in the tumor, they are not necessarily good biomarkers for diagnosis.…”
Section: Ncrna Biomarkersmentioning
confidence: 99%
“…However, major limitations of most studies suggesting lncRNAs as HCC biomarkers are the limited cohort sizes and focusing on only one, sometimes two different HCC etiologies. Only four studies analyzed a total of more than 200 patients 142,151,153,154 and very few studies compared more conditions than HCC vs. healthy control. 142,151,154,155,158 Regarding the heterogeneity of HCC, comparisons between HBV/HCV carriers without HCC, cirrhotic liver condition, early HCC, alcohol-induced HCC, and HBV/HCV-associated HCC are necessary to achieve a comprehensive analysis.…”
Section: Ncrna Biomarkersmentioning
confidence: 99%
“…Additional serum samples from 61 HBV-positive HCC patients, 60 HBV patients, and 60 healthy individuals were also used to validate the diagnostic efficacy of the two lncRNAs. Based on uc001ncr and AX800134 expression, these lncRNAs were determined to accurately diagnose HBV-positive HCC (AUC = 0.9494), including patients with an AFP of 400 ng/ml (AUC = 0.9371), indicating potential usefulness as biomarkers in diagnosing HCC [ 42 ].…”
Section: Dysregulated Lncrnas In the Sera Of Hcc Patientsmentioning
confidence: 99%
“…Recently, lncRNAs have been identified to be specifically expressed or function in the infection of HBV, influenza virus, HIV, and enterovirus 71. [32][33][34][35] There is evidence to show that dynamic changes in chromatin, chromosomes, and nuclear architecture are regulated by lncRNAs. 36 Recent studies have shown that the expression levels of host lncRNAs are changed in response to virus infection.…”
Section: Discussionmentioning
confidence: 99%